(untitled) (Circe de clásicos y modernos, 2018)
The aim of this paper is to study the episode of Aeneid 8 in which Venus asks Vulcan to make an armour for Aeneas. In particular, we are interested in investigating the intertextual relationships which it bears to four passages of the epic tradition: Iliad 18, Iliad 14, Odyssey 8 and Lucretius’ proem to De rerum natura. The analysis of Virgilian imitatiocontributes to the study of the complexity of Venus’ character.